Influence of Dexmedetomidine on Cognitive Function and Inflammatory Factors in Rats and Analysis of Its Molecular Mechanism after Cardiac Surgery under Cardiopulmonary Bypass: Dex effects on cognitive function and inflammatory factors - Dong, Wentao; Li, Xia; Wang, Xiaokang; Cheng, Xiang; Kong, Lingde; Guo, Zhiyong; Jing, Hao (Cellular and Molecular Biology, 2022)
The study aimed to explore the influence of Dexmedetomidine (Dex) on cognitive function and inflammatory factors in rats after cardiac surgery under cardiopulmonary bypass (CPB). For this purpose, 30 healthy male SD rats were reared in a quiet and clean environment with alternating light for 12 hours. They were rolled randomly into 3 groups, each with 10 rats, namely the control (Ctrl) group, the experimental group, and the Dex group. The rats in the Ctrl were not treated, and the rats in the experimental group were intraperitoneally injected with 50μg/kg saline. After that, cardiac surgery was performed under CPB. Rats in the Dex group were injected with 50 μg/kg Dex intraperitoneally and underwent cardiac surgery under CPB. The Morris water maze (MWM) experiment was performed to test the learning and memory abilities and spatial positioning abilities of SD rats. Enzyme-linked immunosorbent assay (ELISA method) was adopted to detect the contents of TNF-α, IL-6, and IL-1β. Fluorescence quantitative PCR was applied to determine the mRNA expression levels of TNF-α, IL-6, and IL-1β in the hippocampus. Results showed that in the MWM experiment, in contrast with the Ctrl, the escape latency of the experimental group and the Dex group after surgery were prolonged (P<0.05), and the times they crossed platforms reduced (P<0.05). In contrast with the experimental group, the escape latency of the Dex group shortened, and the times they crossed platforms increased. ELISA suggested that in contrast with the experimental group, the concentrations of TNF-α, IL-6, and IL-1β in the Ctrl decreased (P<0.05), and those in the Dex group decreased slightly. In the fluorescence quantitative PCR experiment, in contrast with the experimental group, the mRNA expression levels of TNF-α, IL-6, and IL-1β in the Ctrl increased, and those in the Dex group decreased slightly. Then Dex can improve the cognitive dysfunction of rats undergoing cardiac surgery under CPB, and its molecular mechanism may be to reduce the inflammation around the heart and hippocampus.